Comparative Analysis of Inventory Recording Systems Using the Perpetual Method in MSMEs in Medan City - Adinda Chairatunnisa; Nabilla Lubis; Hallisa Amalliya; Suci Abdillah; Henny Andriyani Wirananda (Jurnal EMT KITA, 2026)
This research examines the comparison of three inventory recording methods in a perpetual system, namely FIFO (First In First Out), LIFO (Last In First Out), and the Average method, to understand their impact on the cost of goods sold (COGS), ending inventory value, and net profit. The FIFO method assumes that the items acquired first will be sold or used first, while the LIFO method assumes that the items acquired last will be sold or used first. The Average Method calculates the cost of goods sold based on the average purchase price of inventory. This study applies a quantitative approach with a descriptive comparative method and transaction simulation to evaluate the recording results of the three methods over a specific period. The research findings indicate that the FIFO method results in lower cost of goods sold and higher inventory value, while the LIFO method results in higher COGS and lower inventory value. The Average method provides more stable results among the two. These findings indicate the importance of selecting the appropriate recording method to influence the financial performance and inventory management of trading companies.